The Impact of Radiation Therapy, Lymph Node Dissection, and Hormonal Therapy on Outcomes of Tissue Expander–Implant Exchange in Prosthetic Breast Reconstruction. Issue 1 (January 2016) - Wang, Frederick; Peled, Anne Warren; Chin, Robin; Fowble, Barbara; Alvarado, Michael; Ewing, Cheryl; Esserman, Laura; Foster, Robert; Sbitany, Hani
Abstract : Background: Total skin-sparing mastectomy, with preservation of the nipple-areola complex, must account for adjuvant medical and surgical treatments for cancer. The authors assessed risk factors for complications after second-stage tissue expander–implant exchange. Methods: The authors reviewed all institutional total skin-sparing mastectomy cases that had completed tissue expander–implant exchange with at least 3 months of follow-up. They developed multivariate generalized estimating equation models to obtain adjusted relative risks of radiation therapy, type of lymph node dissection, and hormonal therapy in relation to postoperative complications. Results: The authors performed 776 cases in 489 patients, with a median follow-up of 26 months (interquartile range, 10 to 48 months). Radiation therapy was associated with increased wound breakdown risk [relative risk (RR), 3.3; 95 percent CI, 2.0 to 5.7]; infections requiring oral antibiotics (RR, 2.2; 95 percent CI, 1.31 to 3.6), intravenous antibiotics (RR, 6.4; 95 percent CI, 3.9 to 10.7), or procedures (RR, 8.9; 95 percent CI, 4.5 to 17.5); implant exposure (RR, 3.9; 95 percent CI, 1.86 to 8.3); and implant loss (RR, 4.2; 95 percent CI, 2.4 to 7.4). Axillary lymph node dissection was associated with an increased risk of implant loss (RR, 2.0; 95 percent CI, 1.11 to 3.7) relative to sentinel lymph node biopsy. Conclusions: Axillary lymph node dissection increases the risk of implant loss compared with sentinel lymph node biopsy, independent of radiation therapy. Patients who require axillary lymph node dissection may be encouraged to undergo breast conservation or autologous reconstruction when possible. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.